The partisan politics of law and order - Wenzelburger, Georg (Studies in crime and public policy, 2020)
"Why have some Western democracies experienced a substantial turn toward tougher law and order policies whereas others have not changed their policies to a similar extent? This book shows that an important part of the explanation has to do with political parties and how they compete. It provides empirical evidence on three channels through which partisan politics matter: First, political parties in general, and issue owners in particular, move their programmatic stance toward the more repressive pole if they are challenged by right-wing populist parties or if they are pressured by a major competitor in a two-party system. In contrast, when strong liberal parties exist in a party system and are needed to form coalitions, such a dynamic is much more improbable. Second, a tougher programmatic stance of a party does translate into tougher policies, but only if the institutional context allows for it. Strong constitutional courts are particularly successful in pushing back tougher policies. Finally, the contribution also shows that positive policy feedback occurs: An initial step toward tougher policies may generate a pressure to continue down this road - independent from changes in public opinion. Hence, partisan effects seem to have consequences in the medium term and for future governments. The book bases its arguments on large-N-quantitative analyses of 20 Western industrialized countries as well as a new hand-coded dataset on law and order legislation in Britain, France, Germany and Sweden. Besides, four in-depth case studies on these countries provide qualitative evidence on the politics of law and order"--